(untitled) (Research, Society and Development, 2025)
COVID-19, caused by the coronavirus SARS-CoV-2, was identified in December 2019 in Wuhan, China, following an outbreak of pneumonia. The infection can range from asymptomatic to serious conditions, such as pneumonia and Acute Respiratory Distress Syndrome (ARDS), the main concern. ARDS is classified into levels of severity based on criteria such as time of onset and hypoxemia. SARS-CoV-2 infection causes inflammation and microvascular thrombosis, with emphasis on the "cytokine storm", which worsens the disease, especially in the elderly. Cytokines such as IL-6 and IL-10 are associated with disease severity and their initial levels can help predict prognosis, influencing treatment. The present study aims to carry out a Systematic Literature Review to evaluate the levels of anti-inflammatory cytokines, especially IL-10, in patients with COVID-19 and their relationship with severity, especially in respiratory disorders such as ARDS. The search was carried out in the Pubmed and Lilacs databases, with the inclusion of primary studies and strict eligibility criteria. 197 articles were analyzed, with 13 being considered eligible. The results show that high levels of IL-10 are associated with severe forms of COVID-19, especially elderly patients and patients with comorbidities, who are more susceptible to ARDS. IL-10, in combination with IL-6, can serve as a biomarker to predict disease severity. However, the study has limitations, such as small sample sizes and the lack of comparisons with other inflammatory diseases. Although IL-10 holds promise as an early marker, further studies are needed to confirm its efficacy and determine therapeutic approaches. The combination of cytokines and other clinical findings should be considered in the prognosis of COVID-19.